Protein surface shielding agents in protein crystallization - Hašek, J (Journal of synchrotron radiation, 2011)
The molecules adhering temporarily on the surface of protein molecules change the propensity of protein molecules to deposit on the crystal surface in a definite position and orientation. The concepts of competitive adhesion modes and protein surface shielding agents acting on the surface of molecules in a non-equilibrium process of protein crystallization provide a useful platform for the control of crystallization. The desirable goal, i.e. a transient preference of a single dominating adhesion mode between protein molecules during crystallization, leads to uniform deposition of proteins in a crystal. This condition is the most important factor for diffraction quality and thus also for the accuracy of protein structure determination. The presented hypothesis is a generalization of the experimentally well proven behaviour of hydrophilic polymers on the surface of protein molecules of other compounds.
Keywords: difrakce rentgenového záření; Surface Properties; proteiny; Proteins; Polyethylene Glycols; X-Ray Diffraction; povrchové vlastnosti; hydrofobní a hydrofilní interakce; krystalizace; Hydrophobic and Hydrophilic Interactions; polyethylenglykoly; Crystallization